2019
DOI: 10.1007/s10533-019-00555-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon dioxide and methane fluxes from forests and other land use types in an African tropical montane region

Abstract: In the last 40 years, large areas of the Mau forest, the largest contiguous tropical montane forest in East Africa, have been cleared for agriculture. To date, there are no empirical data on how this land use change affects carbon dioxide (CO 2 ) fluxes from soil respiration and soil methane (CH 4 ) fluxes. This study reports measured annual soil CO 2 and CH 4 fluxes from the native Mau forest and previously forested lands converted to smallholder grazing land, smallholder and commercial tea plantations and eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
52
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 71 publications
15
52
1
Order By: Relevance
“…Furthermore, this can even cause a shift from net uptake to net release of soil CH 4 in some areas of tropics where studies reported net emission of CH 4 from soils within converted ecosystems (Keller et al, ; Simona et al, ). Our results confirmed that the conversion of tropical forest served as an important contributor to atmospheric CH 4 enrichment at large scale (Pendall et al, ; Tate, ; Wanyama et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, this can even cause a shift from net uptake to net release of soil CH 4 in some areas of tropics where studies reported net emission of CH 4 from soils within converted ecosystems (Keller et al, ; Simona et al, ). Our results confirmed that the conversion of tropical forest served as an important contributor to atmospheric CH 4 enrichment at large scale (Pendall et al, ; Tate, ; Wanyama et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…As expected, SOC increased with the C/N ratio (Fig 4A), which is an indicator of the difficulty of soil organic matter decomposition by soil microbes, decreasing decomposition rates of SOC with increasing soil C/N (Wanyama et al, 2019;Xu et al, 2016b). Conversely, total soil N conditioned livestock type effect on SOC in a surprising way.…”
Section: Geophysical Predictors Driving Socsupporting
confidence: 69%
“…In addition to climatic conditions, forest management practices/ land use change could strongly influence soil-atmosphere CO 2 exchange (Ju et al, 2016;Kooch et al, 2016;Wanyama et al, 2019).…”
Section: Effects Of Soil Properties and Microbial Communitymentioning
confidence: 99%
“…We did not find significant relationships between CH 4 fluxes and soil properties across forest types, suggesting the complex effects of factors. It has been reported that soil N availability (i.e., NH 4 + and NO 3 − ) can have positive (Hassler et al, 2015) or negative effects (Wanyama et al, 2019) on methane oxidation. The negative effects are attributed to the competition of NH 4 + and CH 4 for the methane mono-oxygenase enzyme (Wanyama et al, 2019).…”
Section: Ch 4 Fluxmentioning
confidence: 99%
See 1 more Smart Citation